Partitas BWV 825 - 830 - Bach, Johann Sebastian,Levit, Igor (Sony Music, 2014)
Enth.: Partita No. 1 in B-flat major, BWV 825. Partita No. 2 in c minor, BWV 826. Partita No 4 in D Major, BWV 828. Partita No 3 in A minor, BWV 827. Partita No 5 in G Major, BWV 829. Partita No. 6 in E Major, BWV 830
0888430368224
Keywords: CD